ANALISIS YURIDIS KRIMINALISASI LIVING TOGETHER DALAM PERSPEKTIF HAK PRIVASI WARGA NEGARA - Ayu Wulandari; Andy Usmina Wijaya (HUKMY : Jurnal Hukum, 2026)
In the context of protecting citizens' right to privacy, this study discusses the criminalization of living together behavior as regulated in Article 412 of the new Criminal Code (KUHP). In this research, the limits of the state's authority to regulate the private sphere are examined through a normative legal approach, using both statutory and conceptual approaches. The results of the analysis show that the policy of criminalizing living together creates tension between the protection of public morals and respect for individual freedom. Since it does not meet the requirements of the harm principle, this provision potentially violates the principles of proportionality and the ultimum remedium doctrine. Therefore, the policy must be revised to align with the Constitution, the principles of Pancasila, and international human rights standards.